2018
DOI: 10.1155/2018/1743068
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Total Hip Arthroplasty in Two Patients with Charcot Hip Joints due to Congenital Insensivity to Pain with Anhydrosis

Abstract: Traditionally, Charcot arthropathy has been considered an absolute contraindication for total hip arthroplasty (THA). However, some recent reports have shown that good short- to mid-term results can be achieved by improving the durability of the implant. This paper reports the mid- to long-term results of THA in two patients with Charcot hip joints caused by congenital insensivity to pain with anhydrosis. Both patients suffered multiple posterior dislocations in the six months immediately following surgery. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Charcot or neuropathic arthropathy occurs in patients with reduced sensory and nociceptive feedback in a joint susceptible to repetitive microtrauma, leading to progressive joint destruction and deformity [ 65 ]. Five studies met our inclusion criteria which reported upon THA outcomes in the neuropathic or “Charcot” hip population [ [65] , [66] , [67] , [68] , [69] ].…”
Section: Resultsmentioning
confidence: 99%
“…Charcot or neuropathic arthropathy occurs in patients with reduced sensory and nociceptive feedback in a joint susceptible to repetitive microtrauma, leading to progressive joint destruction and deformity [ 65 ]. Five studies met our inclusion criteria which reported upon THA outcomes in the neuropathic or “Charcot” hip population [ [65] , [66] , [67] , [68] , [69] ].…”
Section: Resultsmentioning
confidence: 99%